Становлення кондитерської промисловості в Києві - Коцюбанська, О.О. (Питання історії науки і техніки, 2007)
В статье рассматривается становление кондитерской промышленности г. Киева, его особенности. Использованные архивные материалы по данной теме, в особенности содержащиеся в отчетах Киевского губернатора статистические данные, позволяют представить динамику развития данной отрасли и дают основание утверждать, что именно этот период является периодом становления кондитерского производства Киева как производства промышленного, рассмотреть его негативные и позитивные стороны. Проводятся параллели и сравнения с другими центрами развития этой области промышленности в Украине: Харьковом и Одессой. The paper is devoted to becoming the confectionery industry of Kiev and consideration of its features. The used archival materials on the given theme, in particular contained in from couples of the Kiev governor the statistical data allow to present dynamics of development of the given branch, and give the basis to approve what exactly this period is the period of becoming of confectionery manufacture of Kiev as manufacture industrial, to consider its negative and positive sides. Giving parallels and comparisons with other centers of development of this area of the industry in Ukraine: Kharkov and Odessa.